1944
DOI: 10.1029/tr025i006p00896
|View full text |Cite
|
Sign up to set email alerts
|

Compaction on cultivated soils

Abstract: Many soils which, in their native state were mellow, of low apparent density, and highly permeable to water, have become compact and highly impermeable under cultivation. Other soils, although cultivated as often, still remain fairly permeable. Soils men have long advocated the necessity of reducing the amount of cultivation, and the desirability of selecting a time for field‐operations when the moisture‐content of the soil is such that the bearing power of the soil is adequate to safely carry the equipment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1951
1951
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…In 1959 there were no residual compaction effects on corn yields. 11 wide, 6" long, and 24" deep; points above line AB are for added-fertility, below AB for existing-fertility. r 0~05 = 0.576, r 0 .…”
Section: Resultsmentioning
confidence: 99%
“…In 1959 there were no residual compaction effects on corn yields. 11 wide, 6" long, and 24" deep; points above line AB are for added-fertility, below AB for existing-fertility. r 0~05 = 0.576, r 0 .…”
Section: Resultsmentioning
confidence: 99%
“…Subsoiling has considerable appeal to farmers, but research has shown few benefits from subsoiling in the North Central United States (2,3,8,10), where soils regularly freeze to considerable depth, although some benefits have been reported in the South and Southeast ( 6,7) and in the West (4), where little or no soil freezing occurs. Duley ( 1 ) has summarized the research in the Great Plains and found no evidence of general benefits from subsoiling.…”
mentioning
confidence: 99%
“…Most of the detrimental effects of soil compaction on vegetation were initially studied and characterized in agricultural systems where machinery impacts are high in intensity, frequency, and density [8][9][10]. Since the 1950s, this concern about the detrimental effects of compaction has been extended to forestry [1,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%